1995
DOI: 10.1152/jn.1995.74.1.288
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation of cortical oscillatory dynamics

Abstract: 1. The effect of cholinergic modulation on cortical oscillatory dynamics was studied in a computational model of the piriform (olfactory) cortex. The model included the cholinergic suppression of neuronal adaptation, the cholinergic suppression of intrinsic fiber synaptic transmission, the cholinergic enhancement of interneuron activity, and the cholinergic suppression of inhibitory synaptic transmission. 2. Electroencephalographic (EEG) recordings and field potential recordings from the piriform cortex were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 0 publications
3
53
0
Order By: Relevance
“…Neuromodulators generally have multiple effects in cortical circuits. For instance, they can change the DC firing rate of the neuron 37,38 ; this particular effect can be modelled as an additional depolarizing or hyperpolarizing current. Hence, in the model described above, neuromodulators can in principle alter the DC firing rate so that it approximately matches the oscillation frequency of the network that the neuron is embedded in.…”
Section: Stimulus Locking and Phase Lockingmentioning
confidence: 99%
“…Neuromodulators generally have multiple effects in cortical circuits. For instance, they can change the DC firing rate of the neuron 37,38 ; this particular effect can be modelled as an additional depolarizing or hyperpolarizing current. Hence, in the model described above, neuromodulators can in principle alter the DC firing rate so that it approximately matches the oscillation frequency of the network that the neuron is embedded in.…”
Section: Stimulus Locking and Phase Lockingmentioning
confidence: 99%
“…A number of papers addressed the generation of theta rhythms in the hippocampus using biophysical models (Traub et al, 1992;Liljenstrom and Hasselmo, 1995;Wallenstein and Hasselmo, 1997a,b;Finkel, 1998, 1999). Traub et al (1992) found carbachol-induced theta-frequency oscillations in a model of the CA3 region of hippocampus.…”
Section: Network Oscillation Mechanismsmentioning
confidence: 99%
“…Parameter values used for these simulations are, as far as possible, based on physiological and anatomical data, but some parameters, such as connection weights (synaptic strengths), levels of neuromodulation, etc were not possible to obtain from the experimental data, and had to be tuned. We have previously shown that our cortical neural network model can reproduce essential characteristics of olfactory cortex and hippocampus neurodynamics (Liljenström, 1991(Liljenström, , 1995(Liljenström, , 1997Liljenström and Hasselmo, 1995;Liljenström and Wu, 1995;Å rhem and Liljenström, 2001). It describes intrinsic oscillatory properties of these structures, and reproduces response patterns associated with a continuous random input signal and with a shock pulse given to the cortex.…”
Section: Resultsmentioning
confidence: 97%
“…A mathematical description of the model is summarized below. (A more detailed description with parameter values, etc can be found in Liljenström, 1991;Liljenström and Hasselmo, 1995. ) The time evolution for a network of N neural units is given by a set of coupled nonlinear first-order differential delay equations for all the N internal states, u.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation